Business Failure and the Lottery Syndrome: A Note - Paul E. Adams (Journal of Small Business Finance, 1994)
A significant number of new business failures can be traced to the fact that the founder(s) missed the mark on many of these traits required for success. They may not have inspired confidence in anyone, including themselves. They may have been easily upset by problems. They may have had difficulty in maintaining any internal optimism with no clear vision or realistic goals. Lastly, they may have succumbed to wishful thinking and the need for instant gratification with the material trappings of the business; thus creating an emotional foundation for failure.
Keywords: G33; 650; Failure; Lottery Syndrome; Business Failure